Synthesis and Crystal Engineering of Rubrene and Its Derivatives - Clapham, Margaret L.; Murphy, Emma C.; Douglas, Christopher J. (Synthesis, 2020)
Rubrene (5,6,11,12-tetraphenyltetracene) is a polyacene material that has been well studied throughout its nearly one-hundred year history. Originally found fascinating for its luminescent properties, it has emerged at the forefront for organic electronics due to its particularly high charge carrier mobility for an organic crystal. Despite great interest and its explosion in the literature over the past two decades, the commercial synthesis of rubrene has remained relatively unchanged since its initial discovery in 1926. Several recent studies have reported alternate routes to the rubrene structure with substitutions on the peripheral aromatic rings and tetracene core. Substituting in this manner has the potential to improve upon rubrene’s electronic properties. We review the various routes to rubrene and its derivatives and provide a brief overview of the solid-state library available for study. The information gained by comparing the solid-state properties between derivatives offers insight into unpredictable crystallization and polymorphism – complicated issues – which have hindered research into materials applications of rubrene. We hope that these insights inspire work in application-driven synthetic chemistry for future rubrene derivatives.1 Introduction2 Synthesis2.1 Traditional Rubrene Synthesis2.1.1 Recent Applications2.2 Multi-Step Synthesis2.2.1 Historical Routes2.2.2 Diels–Alder Approaches2.2.3 Cross-Coupling Approaches2.2.4 Comparative Synthesis of Perfluororubrene3 Crystal Engineering4 Conclusions and Outlook
Keywords: rubrene; crystal engineering; comparative synthesis